2016
DOI: 10.1007/s12026-016-8786-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of autoantibodies against aquaporin-5 in the sera of patients with primary Sjögren’s syndrome

Abstract: The pathophysiology of exocrine dysfunction observed in Sjögren’s syndrome (SS) is not fully understood. The purpose of this study was to investigate whether autoantibodies against human AQP5 are present in the sera of SS patients. Frozen sections of mouse submandibular salivary glands, CHO cells over-expressing a human AQP5–GFP fusion protein or GFP, and MDCK cells over-expressing AQP5 were used in the indirect immunofluorescence assay to detect anti-AQP5 autoantibodies in the sera from patients with primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 36 publications
1
47
1
Order By: Relevance
“…To investigate potential roles of the SS-associated species in the pathogenesis of SS, we tested in vitro if selected species of oral bacteria could induce functional and phenotypic changes in SGECs. Three SS-associated bacterial species were selected among the species that are top 30 abundant and contain aquaporins (AQPs) or porins homologous to human AQP 5 [25]: P. histicola, a species associated with SS in both non-dry and dry conditions; and P. melaninogenica and R. mucilaginosa, species associated with SS in the non-dry condition. S. salivarius, the most abundant commensal species in saliva, and F. nucleatum, a highly immune stimulatory species, were additionally included as negative and positive controls, respectively.…”
Section: Deregulation Of Sgecs By P Melaninogenica In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate potential roles of the SS-associated species in the pathogenesis of SS, we tested in vitro if selected species of oral bacteria could induce functional and phenotypic changes in SGECs. Three SS-associated bacterial species were selected among the species that are top 30 abundant and contain aquaporins (AQPs) or porins homologous to human AQP 5 [25]: P. histicola, a species associated with SS in both non-dry and dry conditions; and P. melaninogenica and R. mucilaginosa, species associated with SS in the non-dry condition. S. salivarius, the most abundant commensal species in saliva, and F. nucleatum, a highly immune stimulatory species, were additionally included as negative and positive controls, respectively.…”
Section: Deregulation Of Sgecs By P Melaninogenica In Vitromentioning
confidence: 99%
“…The titers and the local production of anti-SSA and anti-SSB autoantibodies were significantly increased in patients with GC development [41]. The presence of bacteria in the GC-like structures may contribute to the proliferation of B cells and the production of autoantibodies, including anti-AQP5 autoantibodies [25], at local sites through direct stimulation of TLR4 and TLR9 or through exosomes produced from the infected cells. One unanswered question is how neutrophils are not recruited in the presence of bacteria.…”
Section: Plos Onementioning
confidence: 99%
“…Previously, we reported a high degree of homology between AQP5 and AQPZ or porins from many human-associated bacteria, including the members of normal human oral flora (18). The same oral bacterial AQPs presented 35~42% identity and 52~56% similarity with AQP1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Though it was initially proposed from oocyte swelling studies that inhibition of AQP4 water permeability plays a causal role in NMO [11], subsequent studies showed that AQP4-IgGs, even at saturating concentrations, do not inhibit AQP4 water permeability [30]. Interestingly, autoantibodies against AQP2 [17] and AQP5 [1] have been found recently in interstitial nephritis and Sjogren’s syndrome, respectively, though their involvement in disease pathogenesis is not known.…”
Section: 3 Aquaporin Inhibitors – State Of the Fieldmentioning
confidence: 99%